The Master and Margarita - Bulgakov, Mikhail, 1891-1940 (Penguin classics., 2016)
Presents a satirical drama about Satan's visit to Moscow, where he learns that the citizens no longer believe in God. He decides to teach them a lesson by perpetrating a series of horrific tricks. Combines two distinct yet interwoven parts, one set in contemporary Moscow, the other in ancient Jerusalem.